2018
DOI: 10.3390/medsci6020033
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase as an Active Disease Biomarker: Recent Biochemical and Pathological Perspectives

Abstract: Myeloperoxidase (MPO) belongs to the family of heme-containing peroxidases, produced mostly from polymorphonuclear neutrophils. The active enzyme (150 kDa) is the product of the MPO gene located on long arm of chromosome 17. The primary gene product undergoes several modifications, such as the removal of introns and signal peptides, and leads to the formation of enzymatically inactive glycosylated apoproMPO which complexes with chaperons, producing inactive proMPO by the insertion of a heme moiety. The active … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
208
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(222 citation statements)
references
References 207 publications
(194 reference statements)
8
208
0
6
Order By: Relevance
“…Activated neutrophils, monocytes, and some tissue macrophages release MPO at the site of inflammation. MPO catalyzes the reaction between hydrogen peroxide (H 2 O 2 ) and physiological halides (such as Cl − ) to form reactive oxidants such as hypochlorous acid (HOCl) [31]. In this study, EE effectively inhibited the expression of mpo at 20 and 40 µg/mL at 24 h. This suggests that EE has an anti-inflammatory role through the inhibition of leukocyte infiltration.…”
Section: Antioxidant and Anti-inflammatory Activity Of The Ethanol Exmentioning
confidence: 58%
“…Activated neutrophils, monocytes, and some tissue macrophages release MPO at the site of inflammation. MPO catalyzes the reaction between hydrogen peroxide (H 2 O 2 ) and physiological halides (such as Cl − ) to form reactive oxidants such as hypochlorous acid (HOCl) [31]. In this study, EE effectively inhibited the expression of mpo at 20 and 40 µg/mL at 24 h. This suggests that EE has an anti-inflammatory role through the inhibition of leukocyte infiltration.…”
Section: Antioxidant and Anti-inflammatory Activity Of The Ethanol Exmentioning
confidence: 58%
“…MPO is an indicator for neutrophil infiltration . The activation of the neutrophils causes increment of ROS production with subsequent gastric damage .…”
Section: Discussionmentioning
confidence: 99%
“…Prominent increases of TNF α and IL-1 occur within few hours in the inflammatory cascade and may be inadequate for the study for chronic stroke patients [29]. Therefore, IL-6 and MPO were reviewed in the study because they have been reported to be associated with chronic low-grade inflammation and good responses to exercise related anti-inflammatory effects [29,30].…”
Section: Biomarkers Of Oxidative Stress and Pro-inflammation In Plasmamentioning
confidence: 99%